Fishing around the South Georgia Islands and the 'Question of the Falklands/Malvinas': unprecedented challenges for the Antarctic treaty system - Bruno Arpi; Jeffrey McGee (2022)
Despite lying outside the Antarctic Treaty area, the longstanding sovereignty dispute between Argentina and the United Kingdom over the Falklands/Malvinas, South Georgias, and the South Sandwich Islands (collectively known as the 'Question of Falklands/Malvinas') has significant implications for Antarctic governance. The South Georgias and South Sandwich Islands are within the CCAMLR Area and sites of significant fishing interest. Over the last four decades, CCAMLR has been able to avoid any confrontation between Argentina and the UK over regulation of fishing activities in waters surrounding these archipelagos. But at the 2021 CCAMLR meeting, Russia controversially blocked renewal of an existing conservation measure for international management of fishing for Patagonian toothfish in waters surrounding the South Georgias. Under the CCALMR regime, a provision known as the 'Chairman's Statement' allows member states to use national law to regulate fishing in waters surrounding islands within the CCAMLR Area over which state sovereignty is recognised by all Contracting Parties. However, there are differing interpretations on whether the Chairman's Statement allows a CCAMLR state to unilaterally use national law to allow fishing in waters surrounding islands which are under territorial dispute. While CCAMLR has so far avoided addressing this issue, as third parties' interests are involved, it will likely need to take a more active role in the near future. This article therefore assesses the serious challenges this issue raises for CCAMLR and the wider ATS and concludes by presenting paths that the Antarctic community could explore to reduce the present tensions.